Pengaruh Online Customer Review terhadap Keputusan Pembelian Produk Scarlett Whitening pada Pengguna Marketplace Shopee - Wardani, Ailia Dwiyanti Kusuma; Efendi, Erfan Nurkholis (ManBiz: Journal of Management and Business, 2026)
The growth of e-commerce in Indonesia has changed consumer behaviour when making purchasing decisions, including for skincare products such as Scarlett Whitening on Shopee. In this process, online customer reviews have become one of the sources of information consumers use before making a purchase. This study aims to analyze the influence of online customer reviews on the decision to purchase Scarlett Whitening products among Shopee users. The study employed an associative quantitative approach with a sample of 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed via simple linear regression using SPSS. The results indicate that online customer reviews have a positive and significant effect on purchasing decisions, with a regression coefficient of 0.774 and a significance level of < 0.001. The coefficient of determination (R²) of 0.819 indicates that online customer reviews account for 81.9% of the variation in purchasing decisions. These findings suggest that the more positive the online customer reviews consumers receive, the more likely they are to purchase Scarlett Whitening products on Shopee.